2015
DOI: 10.4103/0976-3147.158749
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate use among medical students at Ben-Gurion University of the Negev

Abstract: Introduction:Methylphenidate is a psychotropic agent commonly used for the treatment of attention deficit disorder with or without hyperactivity and narcolepsy in children and adults. The awareness to attention deficit disorder as well as the non-medical use of methylphenidate for cognitive enhancement has increased during the past years.Objectives:To evaluate the medical and non-medical use of methylphenidate among medical students in the Ben-Gurion University of the Negev.Materials and Methods:Medical studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
0
10
0
7
Order By: Relevance
“…Emanuel et al 13 in 2013 reported that 11.0% of medical students from four medical schools in the Chicago area indicated use of cognitive enhancers of which 41.0% used methylphenidate. In 2015, Cohen et al 14 reported that among Israeli medical students, 13.5% indicated methylphenidate use during the past year. Approximately 10.0% of students reported ever being diagnosed with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Emanuel et al 13 in 2013 reported that 11.0% of medical students from four medical schools in the Chicago area indicated use of cognitive enhancers of which 41.0% used methylphenidate. In 2015, Cohen et al 14 reported that among Israeli medical students, 13.5% indicated methylphenidate use during the past year. Approximately 10.0% of students reported ever being diagnosed with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…A eficácia do metilfenidato para seus usos off label varia de limitada a moderada. A maioria desses usos relativamente novos ainda está sendo estudada e implementada na prática clínica (Burgard et al, 2013;Cohen et al, 2015).…”
Section: Indicações Terapêuticas Do Metilfenidato E As Consequências Do Uso Prolongadounclassified
“…Other stimuli included weak parental influence [10], economic uncertainty, peer pressure, and stress [11]. In 2015, another study among Israeli medical students reported that 13.5% admitted to methylphenidate use during the past year [12]. Approximately 10.0% of students reported ever being diagnosed with ADHD.…”
Section: Introductionmentioning
confidence: 99%